1991
DOI: 10.1007/bf02555856
|View full text |Cite
|
Sign up to set email alerts
|

The clearance and bioavailability of pamidronate in patients with breast cancer and bone metastases

Abstract: The pharmacokinetics and bioavailability of pamidronate were assessed in patients with breast cancer, 6 subjects received the drug intravenously and 7 orally. The initial plasma half-life of pamidronate was short (42 +/- 27 min) and the apparent total plasma clearance was high (471 +/- 298 ml/min). The renal clearance (74 +/- 34 ml/min) was similar to the creatinine clearance (66 +/- 19 ml/min). Most of the renal elimination occurred during and immediately post a 4 h infusion of the drug (23.2 +/- 7.9% in 24 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 11 publications
2
29
0
Order By: Relevance
“…These data agree with most other in vitro studies showing maximal growth inhibitory effects of BPs at doses higher than what is persistently achievable in the serum of patients after treatment. In fact, it has been shown that infusion of Pamidronate, which is a less potent antiresorptive BP commonly used in palliative treatments, gives serum concentrations B10-fold lower (0.5 -8 mM) (Daley-Yates et al, 1991;Oiso et al, 1994;Berenson et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…These data agree with most other in vitro studies showing maximal growth inhibitory effects of BPs at doses higher than what is persistently achievable in the serum of patients after treatment. In fact, it has been shown that infusion of Pamidronate, which is a less potent antiresorptive BP commonly used in palliative treatments, gives serum concentrations B10-fold lower (0.5 -8 mM) (Daley-Yates et al, 1991;Oiso et al, 1994;Berenson et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…It is well recognised that the majority of an intravenous infusion of pamidronate is adsorbed onto the bone surface (Daley Yates et al, 1991) where it remains bound to hydroxyapatite for a very long time -probably years. Therefore, a single infusion can theoretically have a prolonged duration of action on the osteoclast, causing sustained inhibition of bone resorption.…”
Section: Disasssionmentioning
confidence: 99%
“…The etidronate and the clodronate, the first agents employed in clinical practice, have been replaced by a second generation of bisphosphonates, the pamidronate and the alendronate, that introduce a greater anti-reabsorption activity in comparison to the previous generation [10, 11, 12, 13]. A third generation of bisphosphonates is now available with the introduction on the market of zoledronate, which is more powerful in both vitro and vivo models of bone re-absorption [14].…”
Section: Introductionmentioning
confidence: 99%